Markov Chain Monte Carlo solutions for radiative transfer problems - Waldenfels, Wilhelm von; Wehrse, Rainer; Baschek, Bodo (Astronomy and astrophysics, 2011)
Algorithms for the solution of the radiative transfer equation that are simultaneously accurate, fast, and easy to implement are still highly desirable, in particular for multidimensional media. We present a stochastic algorithm that solves the transfer equation by assuming that the transfer of radiation can be modelled as a Markov process. It is a generalization of the classical Monte Carlo method and can be applied to the solution of the Milne equation.
Online verfügbar 02 December 2010
Gesehen am 02.11.2022